Generation and Characterization of Acid Tolerant Fibrobacter succinogenes S85 - Chia-wei Wu (Nature Portfolio, 2017)
Abstract Microorganisms are key components for plant biomass breakdown within rumen environments. Fibrobacter succinogenes have been identified as being active and dominant cellulolytic members of the rumen. In this study, F. succinogenes type strain S85 was adapted for steady state growth in continuous culture at pH 5.75 and confirmed to grow in the range of pH 5.60–5.65, which is lower than has been reported previously. Wild type and acid tolerant strains digested corn stover with equal efficiency in batch culture at low pH. RNA-seq analysis revealed 268 and 829 genes were differentially expressed at pH 6.10 and 5.65 compared to pH 6.70, respectively. Resequencing analysis identified seven single nucleotide polymorphisms (SNPs) in the sufD, yidE, xylE, rlmM, mscL and dosC genes of acid tolerant strains. Due to the absence of a F. succinogenes genetic system, homologues in Escherichia coli were mutated and complemented and the resulting strains were assayed for acid survival. Complementation with wild-type or acid tolerant F. succinogenes sufD restored E. coli wild-type levels of acid tolerance, suggesting a possible role in acid homeostasis. Recent genetic engineering developments need to be adapted and applied in F. succinogenes to further our understanding of this bacterium.